The Tightening Accuracy of Workpieces in the Multiple Clamping Devices - Seghedin, Neculai Eugen; Chitariu, Dragoş Florin (Applied Mechanics and Materials, 2014)
Fixtures are used for orientation-positioning-tightening of workpieces during machining on machine tools. Multiple clamping fixtures are intended to clamp several workpieces for simultaneous or successive machining. Multiple clamping is characterized by a series of economical advantages, due to the reduction of total machining time. These advantages are more important once the number of workpieces is higher or if the machining is made with compound tools. Due to the complexity, overall size and the high number of components, the multiple clamping fixtures have diminished accuracy than simple fixture due to elastic and contact deformations of fixtures housing, of supports etc. Also, multiple clamping fixtures present diminished rigidity and dynamic stability. From the analysis of the specialized literature results that there are a few paper on the subject of multiple clamping. In the paper there are presented the causes that can lead to the diminish of the accuracy of multiple fixture. The modalities for the determination of fixtures precision are presented, also, for the parallel and serial multiple clamping fixtures.